Analisis Kinerja Pelaksanaan Administrasi Kependudukan Berbasis E-Government Di Kelurahan Gayungan Kota Surabaya - Nabila Aulia Ayu Rahmatika; Hasan Ismail (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
Public services related to Population Administration are something that the Government must pay attention to its development considering that effective and efficient public services are one of the driving factors for governance, so that innovation is needed in improving the quality of public services. Kelurahan which is an administrative government unit which is only an extension of the city government. Gayungan Village is one of the Village Offices in Surabaya City that implements innovative electronic-based administrative services as a means of managing population administration. Klampid New Generation, which is an online-based application page that can be a solution to problems related to the complicated and lengthy process of managing population documents as a result of the poor performance of public services. In this study, an analysis of the level of effectiveness and efficiency of the use of KNG as a form of improving public services, especially in the Gayungan Village, Surabaya City, was carried out from the many requests submitted and an analysis of the performance of public services was also carried out based on the use of e-government. Using qualitative methods and direct observation based on existing services in the Gayungan Village within a period of four months. The results of this study are that Klampid New Generation as a population administration management service can be said to be successful in its implementation including effectiveness and efficiency in Gayungan Village.